Fasciotomy for Chronic Exertional Compartment Syndrome of the Leg. Issue 1 (13th January 2016) - Owens, Brett D.; Garcia, EStephan J.; Alitz, Curt J.
Abstract : Surgical release of the anterior and lateral compartments of the lower leg has been shown to relieve the symptoms of chronic exertional compartment syndrome. We utilize a technique that allows the surgeon to perform anterior and lateral compartment fasciotomies through a single incision while safely identifying the superficial peroneal nerve. After positioning the patient supine on the operating table with the operative extremity prepared and draped, anatomic landmarks are identified on the patient's skin. The major steps of the procedure are (1) identifying the distal end of the fibula, anterior fibular diaphysis, tibial crest, fibular head, and lateral aspect of the patella; (2) drawing the skin incision, beginning 6 to 8 cm proximal to the distal end of the fibula centered between the tibial crest and anterior fibular diaphysis and extending it 6 cm proximally; (3) making a skin incision longitudinally and dissecting the subcutaneous tissue to allow identification of the fascia and superficial peroneal nerve; (4) performing gentle neurolysis; (5) identifying the anterior and lateral compartments, making small incisions in the fascia of each compartment, and then performing fasciotomy of the lateral and then anterior compartments while protecting the superficial peroneal nerve; and (6) irrigating the wound, closing it in layers, and applying a soft, compressive dressing. Postoperatively, the patient is allowed to bear as much weight as he or she can tolerate. Current literature indicates that good-to-excellent outcomes can be expected for 90% to 95% of patients treated with fasciotomy. Military personnel and patients with posterior compartment involvement may have less reliable outcomes.